Innovative framework for risk management - Saluja, Upasna (2007)
An innovation framework is a global, scalable platform created to harness the creative talents of your employees while staying in alignment with your corporate strategy. It's a strategic approach to innovation from the inside out that provides a way to act on new ideas.